ANALISA PENGARUH KEPERCAYAAN PADA MEREK TERHADAP LOYALITAS MEREK KONSUMEN MOBIL PENUMPANG PRODUK JEPANG DAN KOREA - , Eric Binawan, S. Pt, Bernardinus Maria Purwanto, Dr., M.B.A ([Yogyakarta] : Universitas Gadjah Mada, 2012)
In the competition that getting stronger, every company faces challenges of decreasing customer loyalty due to variety of brand selection and the quality gap decrease. One of the factor that affect to brand loyalty building is brand trust. Korean carâs global performance is already equal with Japanese car, but that condition is not reflected in Indonesia. To find out the cause of weak performance of Korean car brand in Indonesia, analysis of the effect of trust in brand to brand loyalty of Japanese and Korean car was conducted. From the analysis of regression to 100 respondent, found that trust in brand have effect to the bulding of brand loyalty and the difference of brand owning experience is effected to the brand trust variable that affected to brand loyalty building.